3
-1
2
-3
1
Correct answer is E
32y + 6(3y) = 27
This can be rewritten as (3y)2 + 6(3y) = 27
Let 3y = x
x2 + 6x - 27 = 0
(x + 9)(x - 3) = 0
when x - 3 = 0, x = 3
sub. for x in 3y = x
3y = 3
log33 = y
y = 1
If x + 0.4y = 3 and y = 12x, find the value of (x + y)...
The roots of a quadratic equation are −12 and 23. Find the equation....
Find the nth term Un of the A.P., 11, 4, -3,....... . ...
Find the compound interest (CI) on ₦15,700 for 2 years at 8% per annum compounded annually. ...
An arc of a circle subtends an angle of 30° on the circumference of a circle of radius 21cm...
Express 3 - [x−yy] as a single fraction...
If the ratio x:y = 3:5 and y:z = 4:7, find the ratio x:y:z ...